2018
DOI: 10.3390/nu10091201
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea, Coffee, and Caffeine Consumption Are Inversely Associated with Self-Report Lifetime Depression in the Korean Population

Abstract: This study investigated the associations of green tea, coffee, and caffeine consumption with self-report lifetime depression in the Korean population using data from the Korean National Health and Nutrition Examination Survey. In total, 9576 participants (3852 men and 5724 women) aged 19 years or older were selected for the present study. Green tea, coffee, and caffeine consumption levels were assessed with a validated food frequency questionnaire. Multivariate logistic regression analysis was used to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 30 publications
5
60
1
1
Order By: Relevance
“…Only one study has reported relations between coffee consumption and mental health 4 in elderly community-dwelling subjects, and a relation concerning depressive symptoms does not appear to have been investigated. In the research for the non-elderly population, evidence has accumulated indicating that consuming high amounts of coffee is associated with lower depressive symptoms [5][6][7][8][9][10][11][12][13][14] ; however, no association 15,16 and a positive association 17 have also been indicated. Elderly subjects might have different tendencies than non-elderly population.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one study has reported relations between coffee consumption and mental health 4 in elderly community-dwelling subjects, and a relation concerning depressive symptoms does not appear to have been investigated. In the research for the non-elderly population, evidence has accumulated indicating that consuming high amounts of coffee is associated with lower depressive symptoms [5][6][7][8][9][10][11][12][13][14] ; however, no association 15,16 and a positive association 17 have also been indicated. Elderly subjects might have different tendencies than non-elderly population.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the relation between coffee consumption and depressive symptoms in community-dwelling elderly women, in whom this condition is highly prevalent, remains unclear. Several studies have shown that higher amounts of green tea are related to a lower prevalence of depressive symptoms 4,8,10 or psychological distress, 18 whereas green tea was not associated with mental health. 19 Previous studies have reported significant inverse associations between green tea intake and depressive symptoms in a Japanese working population 8 and among Japanese community-dwelling elderly subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a limited number of epidemiological studies have investigated the association between individual constituents and the risk of developing depression [9,10,[20][21][22][23]. The constituents investigated were caffeine and classes of polyphenols found in coffee, including the hydroxycinnamic acids and the falvanoids [9,10,[20][21][22][23]. Mixed results have been obtained, as seen in Table 1 below, suggesting that further investigation into the potential protective nature of these compounds is needed [9,10,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Much of the evidence available comes from epidemiological studies, which generally show a positive effect on mood and cognitive function. Earlier this year, for example, researchers reported that in a healthy Korean population, those who habitually drank green tea were 21% less likely to develop depression over their lifetime than those who were non-drinkers 1 .…”
Section: Benefits Of a Brewmentioning
confidence: 99%